Water Quality Enhancement in Ponds Using Baffles, Burullus in Egypt as a Case Study - Diaa Seif; Medhat Moustafa; Mohamed Soliman (European Scientific Journal, ESJ, 2018)
This study investigated the simulation of hydrodynamics water quality in waste stabilization ponds (WSPs) after using baffles. The major functions performed by baffles are to reduce hydraulic short-circuiting and to provide a submerged surface, which can encourage the growth of attached biomass. Attached biomass growing on the surface of the baffles could increase the total mass of organisms in the pond, thus improve the treatment efficiency and therefore reduce the eutrophication rate in the pond such as NH3-N, NO3-N &PO4-P. In this research, mathematical model (MIKE21) developed by (DHI), was formulated to simulate water quality parameter. The study applied on Burullus Lake, which is the second largest northern lake in Egypt, which belongs to high eutrophic lake type and suffers from several problems. Results showed that there is a significant variance between the rate of values without and after making baffles. The findings indicated that the percentage removal of NH3-N, NO3-N &PO4-P are (51.8, 43.7 &40.1%) respectively in the case of no overlap between baffles, to be (83.4, 94.3 & 89.6%) in the case of overlap ratio 0.95 at the high temperature. This result suggests that the overlap between baffles is more efficient to reduce the eutrophic rate in the water. In conclusion, waste ponds can be improved easily and economically to be more efficient by making baffles.